2016
DOI: 10.3168/jds.2015-10067
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of fertility measured by physical activity traits in Holstein cows

Abstract: Seasonality of female fertility traits, including the interval from calving to first high activity (CFHA), duration of high activity episode (DHA), and strength of high activity episode (SHA) of first estrus, were studied. The physical activity traits were derived from electronic activity tags for 20,794 Holstein cows in 135 commercial Holstein herds in Denmark. Data were categorized in 3 ways: (1) into 4 seasons of calving: winter (January-March), spring (April-June), summer (July-September), and fall (Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Oseni et al (2004) and Ravagnolo and Misztal (2002), who observed low heritability estimates of nonreturn rate when the heat stress level were high using temperature humidity index as a continuous environmental descriptor in the reaction norm model in US Holsteins. Our results were in agreement with those of Ismael et al (2016), who found that heritability of the interval from calving to first high activity (measured from activity tags) for winter calvings was 3 times higher than the heritability for spring and summer calvings Heritability and genetic variance of CFI across different geographic locations were not constant. Heritability estimates decreased with increasing latitude, from LOC-2 to LOC-8, where the heritability estimate obtained for LOC-2 (the highest) was twice the heritability estimate found for LOC-8 (the lowest).…”
Section: Variance Components and Heritability Estimatessupporting
confidence: 92%
See 3 more Smart Citations
“…Oseni et al (2004) and Ravagnolo and Misztal (2002), who observed low heritability estimates of nonreturn rate when the heat stress level were high using temperature humidity index as a continuous environmental descriptor in the reaction norm model in US Holsteins. Our results were in agreement with those of Ismael et al (2016), who found that heritability of the interval from calving to first high activity (measured from activity tags) for winter calvings was 3 times higher than the heritability for spring and summer calvings Heritability and genetic variance of CFI across different geographic locations were not constant. Heritability estimates decreased with increasing latitude, from LOC-2 to LOC-8, where the heritability estimate obtained for LOC-2 (the highest) was twice the heritability estimate found for LOC-8 (the lowest).…”
Section: Variance Components and Heritability Estimatessupporting
confidence: 92%
“…Another possible explanation relates to the directionality of the environmental gradients; that is, whether daylight length and temperature are increasing (January to June) or decreasing (July to December). Such an effect was reported by Ismael et al (2016) on calving to first high activity, who observed that cows calving during the increasing daylight season (January to June) had their first high-activity episode an average of 8 d later than cows calving during the decreasing daylight season (July to December).…”
Section: Effect Of Month Of Calving and Geographic Location On Cfisupporting
confidence: 59%
See 2 more Smart Citations
“…Studies of physical activity derived traits e.g., the interval from calving to the first sign of high activity (CFHA) have reported higher heritability, ranging from 0.12 to 0.18 (Løvendahl and Chagunda, 2009;Ismael et al, 2015). Though CFHA has been suggested as a measure for resumption of ovarian activity, Ismael et al, (2016) showed that a drawback is that activity monitor derived fertility traits are seasonally sensitive.…”
Section: Breeding For Fertilitymentioning
confidence: 99%